2006
DOI: 10.1128/jvi.01435-06
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in the VP1-Unique Region of Native Human Parvovirus B19 Lead to Exposure of Internal Sequences That Play a Role in Virus Neutralization and Infectivity

Abstract: The unique region of the capsid protein VP1 (VP1u) of human parvovirus B19 (B19) elicits a dominant immune response and has a phospholipase A 2 (PLA 2 ) activity, which is necessary for the infection. In contrast to the rest of the parvoviruses, the VP1u of B19 is thought to occupy an external position in the virion, making this region a promising candidate for vaccine development. By using a monoclonal antibody against the most-N-terminal portion of VP1u, we revealed that this region rich in neutralizing epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 41 publications
3
58
1
Order By: Relevance
“…The PLA 2 activity of VP1u is also suspected of contributing to inflammatory processes induced by the production of potent eicosanoid lipid mediators (22). All of these immunological features contrast with our recent findings indicating that the most N-terminal part of VP1u is internal and that the capsids are enzymatically inactive (30). In the present studies we have analyzed the accessibility of the PLA 2 region of VP1u, which is close to the VP1-VP2 junction, and found that this region of VP1u is also internal in native capsids.…”
Section: Discussioncontrasting
confidence: 88%
See 4 more Smart Citations
“…The PLA 2 activity of VP1u is also suspected of contributing to inflammatory processes induced by the production of potent eicosanoid lipid mediators (22). All of these immunological features contrast with our recent findings indicating that the most N-terminal part of VP1u is internal and that the capsids are enzymatically inactive (30). In the present studies we have analyzed the accessibility of the PLA 2 region of VP1u, which is close to the VP1-VP2 junction, and found that this region of VP1u is also internal in native capsids.…”
Section: Discussioncontrasting
confidence: 88%
“…We have previously shown that the most N-terminal part of VP1u, containing neutralizing epitopes, is not exposed on the surface of native B19V particles (30). In the present studies we also show that the PLA 2 region, distant from the N-terminal part, is also not accessible to antibodies.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations